Peningkatan Hasil Belajar Matematika Melalui Model Pembelajaran Probing Prompting - Liny Agustina Silaen (JURNAL GLOBAL EDUKASI, 2018)
Abstract: Based on the observations and experience of Mathematics teachers at SMP Negeri 1 Kisaran, there are many experiencing problems in general learning. However, the main problems in learning Mathematics is the lack of activity and effectiveness of students and student learning outcomes are very less satisfactory. To overcome this problem, Mathematics teacher of SMP Negeri 1 Kisaran performs class action research by choosing action that is changing strategy or learning method. The result of this class action research is the initial condition of the students before it is given the action the average score of students is 59,72. The students who finished 17 with classical completeness reached 47.22%. In cycle I after the final test of the cycle, the average score of student test is 68,05. The total number of students who completed 25 people with climax completeness reached 69.44%. Then in cycle II after the final test of the cycle then got the average score of student test that is 76.67. The total number of students who completed 36 people thoroughly with climax completeness reached 94.44%. The results of this study illustrates that with the use of learning model Probing Prompting can improve the learning outcomes Mathematics material circle on students Class VIII.6 SMP Negeri 1 Kisaran academic year 2016/2017. Keyword: Probing Prompting, circle Abstrak: Berdasarkan hasil pengamatan dan pengalaman guru Matematika di SMP Negeri 1 Kisaran, ada banyak mengalami masalah-masalah dalam pembelajaran umum. Namun yang menjadi masalah utama dalam pembelajaran Matematika adalah kurangnya keaktifan dan efektifitas siswa serta hasil pembelajaran siswa yang sangat kurang memuaskan. Untuk mengatasi hal tersebut, guru Matematika SMP Negeri 1 Kisaran melakukan penelitian tindakan kelas dengan memilih tindakan yaitu mengubah strategi ataupun metode pembelajaran. Adapun hasil dari penelitian tindakan kelas ini adalah kondisi awal siswa sebelum diberi tindakan nilai rata-rata siswa yaitu 59,72. Adapun siswa yang tuntas 17 dengan ketuntasan klasikal mencapai 47,22%. Pada siklus I setelah diadakan tes akhir siklus maka didapatkan nilai rata-rata tes siswa yaitu 68,05. Adapun jumlah siswa yang tuntas 25 orang dengan ketuntasan klaksikal mencapai 69,44%. Kemudian pada siklus II setelah diadakan tes akhir siklus maka didapatkan nilai rata-rata tes siswa yaitu 76,67. Adapun jumlah siswa yang tuntas 36 orang tuntas dengan ketuntasan klaksikal mencapai 94,44%. Hasil penelitian ini menggambarkan bahwa dengan penggunaan model pembelajaran Probing Prompting dapat meningkatkan hasil belajar Matematika materi lingkaran pada siswa Kelas VIII.6 SMP Negeri 1 Kisaran Tahun Pelajaran 2016/2017. Kata kunci: Probing Prompting, lingkaran